Democratic peacebuilding aiding Afghanistan and other fragile states - Ponzio, Richard, 1971- (Oxford : Oxford University Press, 2011)
'Democratic Peacebuilding' considers the evolution of international peacebuilding since the Cold War. It examines, in particular, why international peacebuilders frequently face difficulties in spreading democratic practices and the rule of law in war-torn societies.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Peace-building.; Democratization; Afghanistan -- Politics and government -- 2001-